Representasi Makna Gender dalam Iklan MS Glow x Keanu Analisis Semiotika Ferdinand de saussure - Indriyani Indriyani; Indriati Yulistiani; Juandanilsyah Juandanilsyah; Bayquni Bayquni (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
This study aims to analyze the representation of gender meaning in the MS GLOW x Keanu AGL advertisement titled "Cakep Itu Nasib, Good Looking Itu Pilihan" on YouTube, using Ferdinand de Saussure's semiotic analysis model. This research employs a qualitative approach with semiotic analysis as the method, focusing on identifying the relationship between signifiers and signifieds within five selected scenes of the advertisement. The results of the analysis show that the advertisement constructs gender meaning through two complementary paths: the visual attribute path and the social role path. Through long hair, a pink blazer, a white bathrobe in a bathtub setting, and emotional expression regarding appearance, the advertisement represents men as legitimate subjects in self-care practices and aesthetics. In the perspective of Stuart Hall's representation theory, these signs do not merely reflect social reality, but actively construct new understandings about the relationship between gender and self-care. This representation has implications for marketing communication strategies, showing that inclusive gender representation in advertising can be an effective tool for brand differentiation and market expansion.